2019
DOI: 10.1029/2018jc014762
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Subtropical Mode Water in the Southwestern Atlantic From in Situ Observations

Abstract: We investigated the formation and evolution of the South Atlantic subtropical mode water using data from profiling conductivity, temperature, and depth sensors (CTD) deployed in April–May 2015 and from two customized Argo floats that drifted from April 2015 to June 2017. From the CTD data, we observed a mode water layer below the seasonal thermocline that deepened from the southern side of the area to the north. The two Argo floats remained in the proximity of the cruise area for 2 years. Their slow displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We used the ERA‐5 surface heat flux data distributed by the European Center for Medium‐Range Weather Forecasts (Hersbach et al, ). Previous studies (Ferreira et al, ; Sato & Polito, ) showed a phase delay between the heat flux and the formation cycles. This is a reflection to the fact that it takes time for the ocean to adjust to the heat flux forcing which will precondition it before the mode water formation.…”
Section: Sastmw Interannual Variabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…We used the ERA‐5 surface heat flux data distributed by the European Center for Medium‐Range Weather Forecasts (Hersbach et al, ). Previous studies (Ferreira et al, ; Sato & Polito, ) showed a phase delay between the heat flux and the formation cycles. This is a reflection to the fact that it takes time for the ocean to adjust to the heat flux forcing which will precondition it before the mode water formation.…”
Section: Sastmw Interannual Variabilitymentioning
confidence: 84%
“…The outcropping is a result of vigorous exchange of heat between the ocean and the atmosphere (Talley & McCartney, ; Worthington, ) when both boundary layers experience convective mixing due to that interaction (Marshall et al, ). On the ocean side, the typical winter mixed layer deepens as the surface water sinks due to cooling when the ocean loses heat to the atmosphere (Ferreira et al, ). The amount of water formed is related to the strength and duration of the thermodynamical forcing.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of mesoscale fluctuations in the region is apparent from Figure 6a, where along 39°S, near 39°W and 36°W, there are two cold (SST ≤ 14.1°C) meanders of the South Atlantic Current. To illustrate the effectiveness of the air-sea exchanges to promote a small scale response, Ferreira et al (2019) used TS profiles in the same region, obtained from two customized Argo profilers for a 5-day cycle sampling, and showed a formation event that occurred during one single Argo cycle. In Figure 4a, the area between those limiting contours already has a layer of low PV whose density is such that even a small change in buoyancy flux would be enough to trigger a convective SASTMW formation event (Figure 4d).…”
Section: Changes In the Decorrelation Scalesmentioning
confidence: 99%
“…There are three types of subtropical mode waters identified in that basin. On the western side, the mode water occupies a region between the Brazil Current Recirculation gyre to the north and the Brazil‐Malvinas confluence region to the south (Ferreira et al., 2019). That is the site where the deepest layers of the SASTMWs are formed (Bernardo & Sato, 2020; Santos et al., 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is considered one of the most energetic regions among the oceans (Pezzi et al, 2005). Consequently, we can identify intense gradients of energy and momentum flux, which vertically influence the atmosphere and oceanic thermodynamics, generating deep convective processes leading to vigorous mixing (Ferreira et al, 2019). For these reasons, BMC can be considered an important source of thermostats (Gordon, 1981).…”
Section: Introductionmentioning
confidence: 99%